Pregnancy Toxemia in Ewes: A Review of Molecular Metabolic Mechanisms and Management Strategies - Xiaoyu Ji; Ning Liu; Yuqin Wang; Ke Ding; Shucheng Huang; Cai Zhang (Metabolites, 2023)
Pregnancy toxemia is a nutritional metabolic disease during late gestation in small ruminants. The condition is characterized by disorders in carbohydrate and fat metabolism. Obese and multiparous ewes are particularly susceptible to pregnancy toxemia, which may lead to maternal death, abortion, or premature birth. Highly productive multiparous meat ewes are major breeding animals, which has led to an increased incidence of the disease. However, the pathogenesis of pregnancy toxemia remains unclear and adequate disease prevention and treatment strategies are absent. Investigating the pathogenesis of pregnancy toxemia, especially the metabolic pathways of hepatic lipids, is key to an improved understanding of the condition. This review provides a snapshot of the genes that are associated with lipid metabolism in the ovine liver, including genes involved in fatty acid oxidation, acetyl coenzyme metabolism, and triglyceride synthesis; describes the interrelationships between these genes; and summarizes the diagnosis, prevention, and treatment of pregnancy toxemia.